Composite electrolyte, lithium metal battery including the same, and method for preparing the composite electrolyte
By using a composite electrolyte composed of lithium salt, sulfide or oxide solid electrolytes and low -reactive ionic liquids in lithium metal batteries, the chemical reactions of electrolytes and positive active materials and liquid electrolytes are solved, and higher ion conduction is achieved Rate and battery performance.
Patent Information
- Application Number
- CN201910961958.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-28
- Filing Date
- 2019-10-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2039-10-11
AI Technical Summary
In lithium metal batteries, existing composite electrolytes are prone to chemical reactions with the positive electrode active material and liquid electrolyte, resulting in an increase in interface resistance, a decrease in ion conductivity, and deterioration in battery performance.
The composite electrolytes including lithium salt, sulfides or oxide solid electrolytes and low -reactive ionic liquids are used. By adjusting the electrolyte composition and proportion, the concentration of halogen ions is controlled by less than 25 ppm to reduce the chemical response to the solid electrolyte.
Effectively reduce the interface resistance, improve the ion conduction rate, and improve the energy density, discharge capacity, and high magnification characteristics of lithium metal batteries.
Smart Images

Figure CN111048828B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2018-0122038 filed on October 12, 2018, and Korean Patent Application No. 10-2019-0062580 filed on May 28, 2019, in the Korean Intellectual Property Office, and all rights arising therefrom, the contents of which are incorporated herein in their entirety by reference. Technical Field
[0003] The present disclosure relates to a composite electrolyte, a lithium metal battery including the same, and a method of preparing the composite electrolyte. Background Art
[0004] Metal batteries such as lithium metal batteries generally include a lithium metal film as the negative electrode. Due to the high reactivity of lithium metal, such a lithium metal film is highly reactive to liquid electrolytes during charge and discharge. Therefore, liquid electrolytes may have low stability due to their susceptibility to fire and leakage.
[0005] To improve electrolyte stability, significant attention has been directed toward all-solid batteries using solid electrolytes as non-flammable materials.
[0006] Sulfide or oxide materials can be used as solid electrolytes in all-solid batteries. A drawback in the use of sulfide solid electrolytes may be that reactions occur at the interface between particles of the positive electrode active material and particles of the sulfide solid electrolyte, which may generate interface resistance during charging.
[0007] Therefore, recent attention has been directed toward the use of a composite electrolyte in which a solid electrolyte is mixed with a liquid electrolyte.
[0008] Many of the liquid electrolytes are polar organic solvents, and a chemical reaction may occur between the sulfide solid electrolyte and the liquid electrolyte in the composite electrolyte. As a result, the composite electrolyte may lose ion conductivity and cause deterioration in unit cell performance.
[0009] Therefore, there is a need for improved composite electrolytes, lithium metal batteries including the same, and methods of making the same. Summary of the invention
[0010] Provides a composite electrolyte.
[0011] A lithium metal battery including the composite electrolyte is provided.
[0012] A method for preparing the composite electrolyte is provided.
[0013] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments.
[0014] According to an aspect of one embodiment, a composite electrolyte includes: a lithium salt; a solid electrolyte, wherein the solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof; and an ionic liquid, wherein the mixture of the ionic liquid and the lithium salt includes a dielectric constant of about 4 to about 12, and the amount of halide ions eluted from the composite electrolyte is less than about 25 parts per million (ppm) by weight (by weight) based on the total weight of the composite electrolyte, as measured by ion chromatography.
[0015] According to an aspect of another embodiment, a lithium metal battery includes: a composite positive electrode including a positive electrode collector and a positive electrode active material layer, wherein the positive electrode active material layer is arranged on the positive electrode collector and includes a positive electrode active material and the composite electrolyte; a lithium negative electrode including lithium metal or a lithium alloy; and a composite electrolyte layer between the positive electrode active material layer and the lithium negative electrode and including a lithium salt, an ionic liquid, and a solid electrolyte, wherein the solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof.
[0016] According to an aspect of another embodiment, the method of preparing the composite electrolyte includes combining a lithium salt, a solid electrolyte, and an ionic liquid, wherein the solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] These and / or other aspects will become apparent and more readily appreciated from the following description of the embodiments considered in conjunction with the accompanying drawings, in which:
[0018] Figure 1 A schematic diagram illustrating the structure of a composite positive electrode of a lithium metal battery according to an embodiment;
[0019] Figure 2A and 2B A schematic diagram illustrating the structure of a lithium metal battery according to an embodiment;
[0020] Figure 3 A schematic diagram illustrating the structure of a lithium metal battery according to an embodiment;
[0021] Figure 4 is a graph of intensity (arbitrary unit, au) versus diffraction angle (degrees, 2 theta, degrees, 2θ), illustrating the results of X-ray diffraction analysis of the composite electrolyte and electrolytes according to Example 3 and Comparative Examples 1-3;
[0022] Figure 5is the intensity (arbitrary units) versus wave number (cm -1 , cm -1 ) which illustrates the Raman spectroscopy results of the composite electrolyte and electrolyte according to Example 3 and Comparative Examples 1-3;
[0023] Figure 6 A bar graph illustrating the evaluation results of ionic conductivity of the composite electrolytes and electrolytes according to Examples 1 and 3 and Comparative Examples 1 and 2;
[0024] Fig. 7A is the imaginary impedance (-Z 虚部 , ohms) to the real impedance (Z 实部 , ohms), which shows the impedance evaluation results of the test lithium metal battery according to Comparative Example 10; and
[0025] Figure 7B is the imaginary impedance (-Z 虚部 , ohms) to the real impedance (Z 实部 , ohm) graph showing the impedance evaluation results of the test lithium metal battery according to Example 7. DETAILED DESCRIPTION
[0026] Embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals refer to the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the following description of the embodiments is to illustrate aspects only by reference to the accompanying drawings. As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. "Or" means "and / or". Expressions such as "at least one (kind) of..." modify the entire list of elements when before or after a list of elements without modifying the individual elements of the list.
[0027] It will be understood that when an element is referred to as being “on” another element, it can be directly on the other element or intervening elements may be present therebetween. In contrast, when an element is referred to as being “directly on” another element, there are no intervening elements present.
[0028] In addition, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element as shown in the figure. It will be understood that in addition to the orientation depicted in the figure, relative terms are also intended to cover different orientations of the device. For example, if the device in one of the figures is turned over, the element described as being on the "lower" side of the other element will be oriented on the "upper" side of the other element. Therefore, depending on the specific orientation of the figure, the exemplary term "lower" can cover both "lower" and "upper" orientations. Similarly, if the device in one of the figures is turned over, the element described as "below" or "below" the other element will be oriented "above" the other element. Therefore, the exemplary terms "below..." or "below..." can cover both "above..." and "below..." orientations.
[0029] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "part" discussed below may be referred to as a second element, component, region, layer or part.
[0030] The terms used herein are only for the purpose of describing specific embodiments and are not intended to be limiting. As used herein, the singular forms "a, an" and "said" are intended to include plural forms, including "at least one", unless the content clearly indicates otherwise. "At least one" should not be interpreted as limiting "one". It will be further understood that the terms "comprising" or "including" when used in this specification indicate the presence of stated features, regions, wholes, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more additional features, regions, wholes, steps, operations, elements, components, and / or their collections.
[0031] As used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations relative to the stated value, or within a range of ±30%, 20%, 10%, 5%.
[0032] All ranges disclosed herein are inclusive of the endpoints, and the endpoints are independently combinable with each other (e.g., a range of "up to 25 wt %, or more specifically 5 wt %-20 wt %" includes the endpoints of the range of "5 wt %-25 wt %" and all intermediate values, etc.). Disclosure of a narrower range or more specific grouping in addition to a broader range is not a disclaimer of the broader range or larger grouping. When a range is described as "less than" a recited endpoint, the limitation can be interpreted as greater than 0 to less than the recited endpoint (e.g., "less than 10 ppm" includes "greater than 0 to less than 10 ppm", etc.).
[0033] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as their meanings consistent with their meanings in the context of the present disclosure and the relevant art, and will not be interpreted in an idealized or overly formal sense unless clearly defined in this article.
[0034] The term "C-rate" is a measure of the rate at which a battery is charged or discharged relative to its maximum capacity. A 1C rate or a constant current of 1C means that the charge / discharge current will charge / discharge the entire battery in 1 hour.
[0035] Exemplary embodiments are described herein with reference to cross-sectional views as schematic diagrams of idealized embodiments. Thus, deviations from the shapes of the figures as a result of, for example, manufacturing techniques and / or tolerances are expected. Thus, the embodiments described herein should not be construed as being limited to the specific shapes of the regions as shown herein, but rather include deviations in shape resulting from, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. In addition, the illustrated sharp corners may be rounded. Thus, the regions shown in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shapes of the regions, and are not intended to limit the scope of the claims.
[0036] Hereinafter, a composite electrolyte, a lithium metal battery including the same, and a method of preparing the composite electrolyte according to one or more embodiments of the present disclosure will be described in detail with reference to the accompanying drawings.
[0037] Research has been conducted on a lithium metal battery having a structure in which a liquid electrolyte is filled in a unit cell during manufacture of the unit cell formed of a solid electrolyte as an inorganic material to improve ion conductivity. This structure of the lithium metal battery can increase the capacity of the unit cell and improve high rate characteristics by filling the voids not filled with the solid electrolyte with the liquid electrolyte.
[0038] However, when a sulfide solid electrolyte is used as the solid electrolyte of the lithium metal battery, halogen ions added to improve ion conductivity may be partially eluted due to a reaction between the solid electrolyte and a polar organic solvent, thereby deteriorating the ion conductivity of the solid electrolyte.
[0039] Although attempts have been made to introduce lithium salts at high concentrations to prevent deterioration of ionic conductivity, these attempts have been limited.
[0040] In view of this, the present inventors have developed a novel composite electrolyte.
[0041] A composite electrolyte according to one embodiment includes: a lithium salt; a solid electrolyte, wherein the solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof; and an ionic liquid. The mixture of the ionic liquid and the lithium salt may have a dielectric constant of about 4 to about 12, and the amount of halide ions eluted from the composite electrolyte after the solid electrolyte is immersed in the ionic liquid for 24 hours may be less than about 25 parts per million (ppm) by weight, based on the total weight of the composite electrolyte, as measured by ion chromatography. In other words, 24 hours after the composite electrolyte is assembled, the amount of halide ions present from the composite electrolyte may be less than about 25 ppm.
[0042] By ion chromatography, for example, after the solid electrolyte is immersed in the ionic liquid for 24 hours, the amount of halogen ions eluted from the composite electrolyte can be measured to be less than about 25ppm by weight, based on the total weight of the composite electrolyte. For example, the amount of halogen ions eluted from the composite electrolyte can be less than about 20ppm by weight, or less than about 18ppm by weight, or less than about 15ppm by weight, or less than about 12ppm by weight, or less than about 10ppm, or less than about 8ppm by weight, or less than about 5ppm by weight, or less than about 3ppm by weight, based on the total weight of the composite electrolyte. Any ion chromatography method or equipment available in the art can be used.
[0043] About 14% of the volume of the composite electrolyte is composed of pores or voids formed in the composite electrolyte during the manufacturing process of the battery including the composite electrolyte. These pores or voids can hinder or limit the movement of lithium ions, thereby deteriorating the ionic conductivity of the composite electrolyte. When a polar organic solvent is used to prevent the deterioration of ionic conductivity, as described above, the elution of halogen ions can deteriorate the ionic conductivity. By forming a stable contact interface between the electrode and the solid electrolyte by impregnating the solid electrolyte with an ionic liquid having low chemical reactivity with the solid electrolyte, the composite electrolyte according to the embodiment can maintain or improve ionic conductivity.
[0044] The mixture of the ionic liquid and the lithium salt may have a dielectric constant of about 4 to about 12. For example, the mixture of the ionic liquid and the lithium salt may have a dielectric constant of about 4 to about 11. For example, the mixture of the ionic liquid and the lithium salt may have a dielectric constant of about 4 to about 10. Mixture of Cationic Ionic Liquid and Lithium Salt The mixture of the ionic liquid having a low dielectric constant and the lithium salt may have low reactivity with the solid electrolyte.
[0045] The amount of halogen ions eluted from the composite electrolyte may be less than about 25 ppm by weight based on the total weight of the composite electrolyte. Unlike electrolytes or composite electrolytes according to the related art, the composite electrolyte can reduce the amount of halogen ions eluted, and thus ion conductivity can be maintained or improved.
[0046] The amount of the lithium salt included in the composite electrolyte may be 1 mol / liter (M) or greater. For example, the amount of the lithium salt included in the composite electrolyte may be about 1 M to about 4 M. When the amount of the lithium salt is within these ranges, the mobility of lithium ions in the composite electrolyte may be increased, and thus the ionic conductivity may be improved.
[0047] The lithium salt may include LiSCN, LiN(CN) 2 、Li(CF 3 SO 2 ) 3 C. LiC 4 F 9 SO 3 、LiN(SO 2 CF 2 CF 3 ) 2 , LiCl, LiF, LiBr, LiI, LiB(C 2 O 4 ) 2 (Lithium bis(oxalato)borate, LiBOB), LiBF 4 , LiBF 3 (C 2 F 5 ), lithium difluoro(oxalate)borate (LiDFOB, lithium oxalyldifluoroborate, LIODFB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, LiN(SO 2 CF 3 ) 2 ), lithium bis(fluorosulfonyl)imide (LiFSI, LiN(SO 2 F) 2 )、LiCF 3 SO 3, LiAsF 6 , LiSbF 6 , LiClO 4 , or a combination thereof. For example, the lithium salt may be a lithium imide salt. Examples of the lithium imide salt may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, LiN(SO 2 CF 3 )) 2 and lithium bis(fluorosulfonyl)imide (LiFSI, LiN(SO 2 F) 2 ). Since the lithium salt appropriately maintains the chemical reactivity with the ionic liquid, the ionic conductivity can be maintained or improved.
[0048] The weight ratio of the solid electrolyte to the ionic liquid may be from about 0.1:99.9 to about 90:10. For example, the weight ratio of the solid electrolyte to the ionic liquid may be from about 10:90 to about 90:10. For example, the weight ratio of the solid electrolyte to the ionic liquid may be from about 20:80 to about 90:10. For example, the weight ratio of the solid electrolyte to the ionic liquid may be from about 30:70 to about 90:10. For example, the weight ratio of the solid electrolyte to the ionic liquid may be from about 40:60 to about 90:10. For example, the weight ratio of the solid electrolyte to the ionic liquid may be from about 50:50 to about 90:10. When the weight ratio is within the above range, the composite electrolyte expands or increases the electrochemical contact area with the electrode, thereby maintaining or improving the ionic conductivity. A battery including the composite electrolyte may have a high energy density, a high capacity, and excellent high-rate characteristics.
[0049] The sulfide solid electrolyte may include a solid electrolyte represented by the following Formula 1.
[0050] Formula 1
[0051] Li a M b PS c A d
[0052] In Formula 1, 0 < a ≤ 6, 0 ≤ b ≤ 6, 0 < c < 6, and 0 ≤ d ≤ 6; M may be Ge, Sn, or Si; and A may be F, Cl, Br, or I.
[0053] Since the solid electrolyte represented by Formula 1 has a high ionic conductivity similar to that of the liquid electrolyte in the related art (which is in the range of about 10 -2 Siemens / cm (S / cm) - about 10 -3 S / cm at room temperature), the composite electrolyte including the solid electrolyte may have improved ionic conductivity.
[0054] Optionally, the sulfide solid electrolyte may include a solid electrolyte containing sulfur and lithium and further containing the following elements: the elements are phosphorus (P), silicon (Si), boron (B), aluminum (Al), germanium (Ge), zinc (Zn), gallium (Ga), indium (In), tin (Sn), fluorine (F), chlorine (Cl), bromine (Br), iodine (I), or a combination thereof. The solid electrolyte may include the following compounds: they are lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide, or a combination thereof. The solid electrolyte can improve the electrochemical stability.
[0055] For example, the sulfide solid electrolyte may further include a sulfide in the form of thio-LISICON such as Li 10 GeP 2 S 12 . By including a sulfide in the form of thio-LISICON, the composite electrolyte may have further improved ionic conductivity.
[0056] For example, the oxide solid electrolyte may include Li 1+x Ti 2-x Al(PO 4 ) 3 (LTAP, where 0 ≤ x ≤ 4), Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (where 0 < x < 2 and 0 ≤ y < 3), BaTiO 3 , Pb(Zr 1-a Ti a )O 3 (PZT, where 0 ≤ a ≤ 1), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT, where 0 ≤ x < 1 and 0 ≤ y < 1), Pb(Mg 1 / 3 Nb 2 / 3 )O 3 -PbTiO 3 (PMN-PT), HfO 2 , SrTiO 3 , SnO 2 , CeO 2 , Na 2 O, MgO, NiO, CaO, BaO, ZnO, ZrO 2 , Y 2 O 3 , Al 2O 3 , TiO 2 , SiO 2 , lithium phosphate (Li 3 PO 4 ), lithium titanium phosphate (Li x Ti y (PO 4 ) 3 , where 0 < x < 2 and 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO 4 ) 3 , where 0 < x < 2, 0 < y < 1, and 0 < z < 3), Li 1+x+y (Al 1-a Ga a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O 12 (where 0 ≤ a ≤ 1, 0 ≤ b ≤ 1, 0 ≤ x ≤ 1, and 0 ≤ y ≤ 1), lithium lanthanum titanate (Li x La y TiO 3 , where 0 < x < 2 and 0 < y < 3), Li 2 O, LiAlO 2 , Li 2 O - Al 2 O 3 - SiO 2 - P 2 O 5 - TiO 2 - GeO 2 ceramics, garnet ceramics (Li 3+x La 3 M 2 O 12 , where M is Te, Nb, or Zr), or a combination thereof. In addition to the above oxide solid electrolytes, the oxide solid electrolyte may further include any oxide inorganic particles and / or oxide solid electrolytes available in the art.
[0057] The ionic liquid may include a heterocyclic cationic compound having a saturated 5- to 12-membered ring, including a heteroatom in the heterocyclic ring, wherein the heteroatom is nitrogen (N), phosphorus (P), arsenic (As), or a combination thereof. The ionic liquid may reduce the chemical reactivity with the sulfide solid electrolyte. In comparison, an ionic liquid including a cation having an unsaturated 5- to 12-membered heterocyclic ring as a core decomposes due to a reaction with the sulfide solid electrolyte. Therefore, a composite electrolyte including the same may have a reduced ionic conductivity.
[0058] For example, the ionic liquid may include a cation represented by Formula 2, Formula 3, or a combination thereof.
[0059] Formula 2
[0060]
[0061] Formula 3
[0062]
[0063] In Formulae 2 and 3, X may independently be N or P; R 1 , R 2 , R 7 , and R 8 R may be independently a substituted or unsubstituted C1-C30 alkyl group or a substituted or unsubstituted C2-C20 alkenyl group; 3 , R 4 , R 5 , R 6 , R 9 , R 10 , R 11 , R 12 , and R 13 can be independently hydrogen, halogen, hydroxyl, cyano, -C(=O)R a 、-C(=O)OR a 、-OCO(OR a )、-C=N(R a ),-SR a 、-S(=O)R a 、-S(=O) 2 R a 、-OR a , substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted C2-C20 alkenyl, substituted or unsubstituted C2-C20 alkynyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C6-C30 aryloxy, substituted or unsubstituted C6-C30 heteroaryl, or any combination thereof, wherein each R aare independently hydrogen, C1-C10 alkyl, or C6-C20 aryl; and R 1 and R 2 At least one of them is an unsubstituted C1-C10 alkyl group, and R 7 and R 8 At least one of the groups is an unsubstituted C1-C10 alkyl group.
[0064] For example, in Equations 2 and 3, R 1 and R 2 At least one of may be an unsubstituted C3-C10 alkyl group, and R 7 and R 8 At least one of the groups is an unsubstituted C3-C10 alkyl group.
[0065] The term "substituted" as used in Formulas 2 and 3 means that at least one hydrogen atom of the functional group is replaced by a halogen atom, a C1-C10 alkyl group substituted by a halogen atom (e.g., CF 3 , CHF 2 , CH 2 F、CCl 3 The invention also includes but is not limited to alkyl, aryl, aryl, arylalkyl, aryloxy, aryloxyalkyl ...
[0066] The term "halogen" includes F, Br, Cl, and I.
[0067] The term "alkyl" refers to a fully saturated, branched or unbranched (or straight chain or linear) monovalent hydrocarbon group. Examples of "alkyl" may include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, 3-methylhexyl, 2,2-dimethylpentyl, 2,3-dimethylpentyl, and n-heptyl. The term "alkylene" refers to a divalent alkyl group.
[0068] The term "alkoxy" refers to an alkyl group attached to an oxygen atom. Examples of "alkoxy" may include, but are not limited to, methoxy, ethoxy, and propoxy.
[0069] The term "alkenyl" refers to a branched or unbranched hydrocarbon group having at least one carbon-carbon double bond. Examples of alkenyl groups may include, but are not limited to, vinyl, allyl, butenyl, isopropenyl, or isobutenyl.
[0070] The term "alkynyl" refers to a branched or unbranched hydrocarbon group having at least one carbon-carbon triple bond. Examples of "alkynyl" may include, but are not limited to, ethynyl, butynyl, isobutynyl, and isopropynyl.
[0071] The term "cycloalkyl" refers to a generally saturated, monovalent, non-aromatic group in the form of a monocyclic or bicyclic hydrocarbon group of 3 to 10 atoms. Examples of "cycloalkyl" may include, but are not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cyclooctyl.
[0072] The term "aryl" refers to an aromatic group in which the aromatic ring includes at least one carbocyclic ring. Examples of "aryl" may include, but are not limited to, phenyl, naphthyl, and tetrahydronaphthyl.
[0073] The term "aryloxy" refers to a monovalent group of the form Ar-O, wherein Ar is an aryl group. Examples of "aryloxy" may include, but are not limited to, phenoxy.
[0074] The term "heteroaryl" refers to a monocyclic or bicyclic aromatic group in which at least one ring atom is a heteroatom selected from N, O, P, and S and the remaining ring atoms are carbon atoms. For example, a "heteroaryl" group may include 1-5 heteroatoms and 5-10 ring members. Here, S or N may be oxidized to form a variety of oxidation states.
[0075] Examples of "heteroaryl" may include, but are not limited to, thienyl, furanyl, pyrrolyl, imidazolyl, pyrazolyl, thiazolyl, isothiazolyl, 1,2,3- Oxazolyl, 1,2,4- Oxazolyl, 1,2,5- Oxazolyl, 1,3,4- oxadiazole, 1,2,3-thiadiazolyl, 1,2,4-thiadiazolyl, 1,2,5-thiadiazolyl, 1,3,4-thiadiazolyl, isothiazol-3-yl, isothiazol-4-yl, isothiazol-5-yl, Oxazol-2-yl, Oxazol-4-yl, oxazol-5-yl, isoxazol-5-yl Oxazol-3-yl, iso Oxazol-4-yl, iso oxazol-5-yl, 1,2,4-triazol-3-yl, 1,2,4-triazol-5-yl, 1,2,3-triazol-4-yl, 1,2,3-triazol-5-yl, tetrazolyl, pyridin-2-yl, pyridin-3-yl, pyrazin-2-yl, pyrazin-4-yl, pyrazin-5-yl, pyrimidin-2-yl, pyrimidin-4-yl, and pyrimidin-5-yl.
[0076] As used herein, the term "carbocycle (type)" refers to a saturated or partially unsaturated non-aromatic monocyclic, bicyclic or tricyclic hydrocarbon group. The limiting examples of monocyclic hydrocarbon groups include cyclopentyl, cyclopentenyl, cyclohexyl and cyclohexenyl. The limiting examples of bicyclic hydrocarbon groups include bornyl, decahydronaphthyl, bicyclic [2.1.1] hexyl, bicyclic [2.2.1] heptyl, bicyclic [2.2.1] heptenyl and bicyclic [2.2.2] octyl. The tricyclic hydrocarbon group can be, for example, adamantyl etc.
[0077] As used herein, the term "heterocycle" refers to a cyclic group having at least one heteroatom and 5 to 20 carbon atoms, for example, 5 to 10 carbon atoms. In this regard, the heteroatom may be one selected from sulfur, nitrogen, oxygen, and boron.
[0078] For example, the anion of the ionic liquid may include BF 4 - , AsF 6 - , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2 - ,(CF 3 SO 2 ) 3 C - 、NO 3 - , CH 3 COO - , Cl - Br - ,I - 、SO 4 2- CF 3 SO 3 - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - ,(CF 3 )3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - , SF 5 CF 2 SO 3 - , SF 5 CHF 2 SO 3 - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - , C 2 N 3 - , and (O(CF 3 ) 2 C 2 (CF 3 ) 2 O) 2 PO - 、(FSO 2 ) 2 N - ,(CF 3 SO 2 ) 2 N - , or any mixture thereof.
[0079] The composite electrolyte may further include a liquid electrolyte, a polymer ionic liquid, or a combination thereof.
[0080] The liquid electrolyte may include a lithium salt and an organic solvent. The organic solvent may be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an amine solvent, or a phosphine solvent. For example, the organic solvent may include ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, γ-butyrolactone, dimethoxyethane, diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol dimethyl ether, succinonitrile, cyclopentane sulfone, dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, adiponitrile, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, or a combination thereof. For example, the organic solvent may include dimethoxyethane, diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, or a combination thereof.
[0081] The polymer ionic liquid may be a polymer obtained by polymerizing an ionic liquid monomer or a compound in polymer form. The polymer ionic liquid has high solubility in an organic solvent and can further improve ionic conductivity when added to an electrolyte. When the polymer ionic liquid is obtained by polymerizing an ionic liquid monomer, the polymer product may be washed and dried, and then anion replacement may be performed to have anions that will dissolve in an organic solvent.
[0082] The polymeric ionic liquid may include repeating units comprising: a cation such as an ammonium cation, a pyrrolidine Cation, piperidine Cation, Imidazole Cation, pyrazole cation, Azoles Cation, Pyridazine cation, Cation, sulfonium cation, triazole cations, or combinations thereof, and anions such as BF 4 - , AsF 6 - , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2- 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、Cl - 、Br - 、I - 、SO 4 2- 、CF 3 SO 3 - 、(C 2 F 5 SO 2 ) 2 N - 、(C 2 F 5 SO 2 )(CF 3 SO 2 )N - 、NO 3 - 、Al 2 Cl 7 - 、(CF 3 SO 2 ) 3 C - 、(CF 3 ) 3 PF 3 - 、(CF 3 ) 4 PF 2 - 、(CF 3 ) 5 PF - 、(CF 3 ) 6 P - 、SF 5 CF 2 SO 3 - 、SF 5 CHFCF 2 SO 3 - 、CF 3 CF 2 (CF 3 ) 2 CO - 、(CF 3 SO 2 ) 2 CH -, (SF 5 ) 3 C - ,(O(CF 3 ) 2 C 2 (CF 3 ) 2 O) 2 PO - , or a combination thereof.
[0083] Alternatively, the polymeric ionic liquid may be prepared via polymerization of an ionic liquid monomer. The ionic liquid monomer may have a polymerizable functional group such as a vinyl group, an allyl group, an acrylate group, and a methacrylate group and also have: a cation such as an ammonium cation, a pyrrolidone cation, a Cation, piperidine cations, etc., or combinations thereof; and any of the above anions.
[0084] For example, the polymer ionic liquid may be a compound represented by Formula J or a compound represented by Formula K.
[0085] Formula J
[0086]
[0087] In formula J, R" 1 and R" 3 may be each independently hydrogen, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C2-C30 heteroaryl, or substituted or unsubstituted C4-C30 carbocyclic group, R" 2 It can be a simple chemical bond, a C1-C30 alkylene group, a C6-C30 arylene group, a C2-C30 heteroarylene group, or a C4-C30 divalent carbocyclic group. - may be an anion of the polymeric ionic liquid, and n may be from about 500 to about 2,800.
[0088] Formula K
[0089]
[0090] In formula K, Y - With formula J Z - The same is defined, and n may be from about 500 to about 2800.
[0091] In formula K, Y - For example, bis(trifluoromethanesulfonyl)imide (TFSI), bis(fluorosulfonyl)imide, BF 4 -, or CF 3 SO 3 - .
[0092] Examples of the compound represented by the above Formula K may include poly(bis(trifluoromethanesulfonyl)imidediallyldimethylammonium).
[0093] The substituents and functional groups used in the compounds represented by Formulae J and K are as defined above, and thus a detailed description thereof will not be given.
[0094] According to another embodiment, a lithium metal battery includes: a composite positive electrode, which includes a positive electrode collector and a positive electrode active material layer disposed on the current collector and containing a positive electrode active material and the above-mentioned composite electrolyte; a lithium negative electrode including lithium metal or a lithium alloy; and a composite electrolyte layer between the positive electrode active material layer and the lithium negative electrode and including a lithium salt, an ionic liquid, and a solid electrolyte, wherein the solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof.
[0095] Since the lithium metal battery includes an ionic liquid having reduced chemical reactivity with the composite electrolyte, a stable contact interface can be formed between the composite positive electrode and the composite electrolyte layer and a sufficient interface area can be obtained. As a result, sufficient lithium ion channels are obtained in the lithium metal battery, and thus ion conductivity can be maintained or improved. The energy density and discharge capacity of the lithium metal battery can be increased, and in addition, high rate characteristics and life characteristics can also be improved.
[0096] Positive electrode active material layer
[0097] In the positive electrode active material layer, the amount of the positive electrode active material may be about 60 parts by weight or more, based on 100 parts by weight of the positive electrode active material layer. For example, in the positive electrode active material layer, the amount of the positive electrode active material may be about 60 parts by weight to about 90 parts by weight, based on 100 parts by weight of the positive electrode active material layer. When the positive electrode active material layer includes a sufficient amount of the positive electrode active material within the above range, a lithium metal battery including the positive electrode active material layer may have a high mixture density and a high energy density.
[0098] Any compound allowing intercalation / deintercalation of lithium ions used in the art may be used as the positive electrode active material without limitation.
[0099] Examples of the compound that allows insertion / deinsertion of lithium ions may include one of the compounds represented by the following formulae: Li a A' 1-b B' b D' 2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Lia E' 1-b B' b O 2-c D' c (where 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); LiE' 2-b B' b O 4-c D' c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b- c Co b B' c D' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c D' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni b E' c G' d O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1); Li a Ni b Co c Mn d G' e O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1); Li a NiG' b O 2(where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG' b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a MnG' b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 2 G' b O 4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Q'O 2 ;Q'S 2 ;LiQ'S 2 ; V 2 O 5 ;LiV 2 O 5 ;LiI'O 2 ;LiNiVO 4 ;Li (3-f) J' 2 (PO 4 ) 3 (where 0≤f≤2); Li (3-f) Fe 2 (PO 4 ) 3 (where 0≤f≤2); and LiFePO 4 .
[0100] In the above formula, A' may be Ni, Co, Mn, or any combination thereof; B' may be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or any combination thereof; D' may be O, F, S, P, or any combination thereof; E' may be Co, Mn, or any combination thereof; F' may be F, S, P, or any combination thereof; G' may be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or any combination thereof; Q' may be Ti, Mo, Mn, or any combination thereof; I' may be Cr, V, Fe, Sc, Y, or any combination thereof; and J' may be V, Cr, Mn, Co, Ni, Cu, or any combination thereof.
[0101] The compounds listed above may have a coating layer on their surface, or a mixture of a compound without a coating layer and a compound with a coating layer may be used. The coating layer may include a compound of a coating element, such as an oxide, hydroxide, oxyhydroxide, oxycarbonate or hydroxycarbonate of the coating element. The compound constituting the coating layer may be amorphous or crystalline. Examples of the coating elements included in the coating layer may be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a combination thereof. Any coating method (e.g., spraying and impregnation) that does not adversely affect the physical properties of the positive active material may be used as a process for forming the coating layer. These methods are clear to those of ordinary skill in the art, and a detailed description thereof will not be given.
[0102] For example, the positive electrode active material may be a nickel composite oxide including 60 wt % or more of nickel such as lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide. These positive electrode active materials containing nickel can easily have ion conductivity because no resistive component is generated between the positive electrode active material containing nickel and the sulfide solid electrolyte.
[0103] For example, in addition to the nickel composite oxide, the positive electrode active material may also be lithium cobalt oxide (LiCoO 2 For example, the positive electrode active material may be a material obtained by mixing lithium cobalt oxide with nickel composite oxide, LiNbO 2 , Li 4 Ti 5 O 12 A composite positive electrode active material prepared by coating with aluminum oxide, etc.
[0104] In the positive electrode active material layer, the amount of the composite electrolyte may be about 5 parts by weight or more, based on 100 parts by weight of the positive electrode active material layer. For example, in the positive electrode active material layer, the amount of the composite electrolyte may be about 6 parts by weight or more, based on 100 parts by weight of the positive electrode active material layer. For example, in the positive electrode active material layer, the amount of the composite electrolyte may be about 7 parts by weight or more, based on 100 parts by weight of the positive electrode active material layer. For example, in the positive electrode active material layer, the amount of the composite electrolyte may be about 8 parts by weight or more, based on 100 parts by weight of the positive electrode active material layer. For example, in the positive electrode active material layer, the amount of the composite electrolyte may be about 40 parts by weight or less, based on 100 parts by weight of the positive electrode active material layer. For example, the amount of the composite electrolyte may be about 5 to about 40 parts by weight, or about 6 to about 40 parts by weight, or about 7 to about 40 parts by weight, or about 8 to about 40 parts by weight, based on 100 parts by weight of the positive active material layer.
[0105] The positive active material layer may further include a conductive agent, a binder, or both a conductive agent and a binder.
[0106] The conductive agent may be, but is not limited to, carbon black, graphite, natural graphite particles, artificial graphite, acetylene black, Ketjen black, carbon fibers, or carbon nanotubes; metals such as copper, nickel, aluminum, and silver in the form of powder, fiber, or tube; or conductive polymers such as polyphenylene derivatives, or any conductive material available in the art may also be used.
[0107] The binder may be, but is not limited to, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene-butadiene rubber, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer, polychlorotrifluoroethylene, vinylidene fluoride-pentafluoropropylene copolymer, propylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene copolymer, or ethylene-acrylic acid copolymer, each of which may be used alone or in combination with each other, and any binder available in the art may also be used.
[0108] The amounts of the conductive material and the binder may be the same as those used in a lithium metal battery.
[0109] Figure 1 Schematic diagrams illustrating composite cathodes 10 and 10' of a lithium metal battery according to an embodiment. The composite cathode 10 illustrates a state before an ionic liquid is added, and the composite cathode 10' illustrates a state after an ionic liquid is added.
[0110] Reference Figure 1, the composite positive electrode 10 or 10' comprises: a positive electrode current collector 1 or 1'; and a positive electrode active material layer 8 or 8', which comprises a plurality of positive electrode active material particles 2 or 2' and a plurality of solid electrolyte particles 3 or 3' selected from sulfide solid electrolytes and oxide solid electrolytes, both of which are respectively arranged on the positive electrode current collector 1 or 1'. In the composite positive electrode 10, there are a plurality of pores 4 located between adjacent positive electrode active material particles 2 or 2', between adjacent positive electrode active material particles 2 or 2' and solid electrolyte particles 3 or 3', between adjacent solid electrolyte particles 3 or 3', or a combination thereof. In the composite positive electrode 10', at least one of the pores 4 is filled with an ionic liquid 5. In other words, the ionic liquid is arranged in at least one pore between adjacent positive electrode active material particles, in at least one pore between adjacent positive electrode active material particles and solid electrolyte particles, in at least one pore between adjacent solid electrolyte particles, or a combination thereof. The term "pore" refers to a hole, space, or void formed between mixed particles of positive electrode active material particles 2 and solid electrolyte particles 3. In an embodiment, substantially all of the pores 4 of the composite cathode 10 are filled with (eg, contain) the ionic liquid 5 to provide a composite cathode 10 ′.
[0111] The ionic liquid 5 filled or disposed in the pores 4 can reduce or prevent the formation of a resistance layer caused by a reaction (side reaction) between the transition metal element, oxygen, and sulfur present on the surfaces of the particles 3 and 3' of the sulfide solid electrolyte present on the surfaces of the positive electrode active material particles 2 and 2'. Therefore, a lithium ion channel can be established, and the ion conductivity of the lithium metal battery including the same can be maintained or improved.
[0112] In the positive electrode active material layer of the composite positive electrode, after maintaining for 100 hours, the ionic conductivity of the composite electrolyte can be reduced by about 15% or less relative to the initial ionic conductivity. As used herein, the term "maintain" means to maintain at an open circuit voltage. The measure of the reduction in ionic conductivity can be expressed as an ionic conductivity reduction rate (%) according to Equation 1.
[0113] Equation 1
[0114] Ion conductivity reduction rate (%) = [(initial ion conductivity - ion conductivity after 100 hours of maintenance) / (initial ion conductivity)] x 100%
[0115] Composite electrolyte layer
[0116] The composite electrolyte layer includes: a lithium salt; an ionic liquid; and a solid electrolyte, which is a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof.
[0117] In the composite electrolyte layer, an amount of the ionic liquid may be less than about 50 parts by weight based on 100 parts by weight of the composite electrolyte layer.
[0118] Since the compositions of the sulfide solid electrolyte and the oxide solid electrolyte included in the composite electrolyte layer are as described above, a detailed description thereof will not be given.
[0119] In the composite electrolyte layer, the lithium salt may include LiSCN, LiN(CN) 2 、Li(CF 3 SO 2 ) 3 C. LiC 4 F 9 SO 3 、LiN(SO 2 CF 2 CF 3 ) 2 , LiCl, LiF, LiBr, LiI, LiB(C 2 O 4 ) 2 (Lithium bis(oxalato)borate, LiBOB), LiBF 4 , LiBF 3 (C 2 F 5 ), lithium difluoro(oxalato)borate (LiDFOB, lithium difluorooxalate oxalyl, LIODFB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, LiN(SO 2 CF 3 ) 2 ), lithium bis(fluorosulfonyl)imide (LiFSI, LiN(SO 2 F) 2 )、LiCF 3 SO 3 、LiAsF 6 、LiSbF 6 、LiClO 4 or any mixture thereof. For example, the lithium salt may be an imide lithium salt. Examples of the imide lithium salt may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, LiN(SO 2 CF 3 ) 2 ) and lithium bis(fluorosulfonyl)imide (LiFSI, LiN(SO 2 F) 2 ). The lithium salt appropriately maintains chemical reactivity with the ionic liquid, thereby maintaining or improving ionic conductivity.
[0120] In the composite electrolyte layer, the ionic liquid may include a cation represented by Formula 2, Formula 3, or a combination thereof.
[0121] Formula 2
[0122]
[0123] Formula 3
[0124]
[0125] In Formulae 2 and 3, X may independently be N or P; R 1 , R 2 , R 7 , and R 8 R may be independently a substituted or unsubstituted C1-C30 alkyl group or a substituted or unsubstituted C2-C20 alkenyl group; 3 , R 4 , R 5 , R 6 , R 9 , R 10 , R 11 , R 12 , and R 13 can be independently hydrogen, halogen, hydroxyl, cyano, -C(=O)R a 、-C(=O)OR a 、-OCO(OR a )、-C=N(R a ),-SR a 、-S(=O)R a 、-S(=O) 2 R a 、-OR a , substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted C2-C20 alkenyl, substituted or unsubstituted C2-C20 alkynyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C6-C30 aryloxy, substituted or unsubstituted C6-C30 heteroaryl, or any combination thereof, wherein each R a are independently hydrogen, C1-C10 alkyl, or C6-C20 aryl; and R 1 and R 2 At least one of them is an unsubstituted C1-C10 alkyl group, and R 7 and R 8 At least one of the groups is an unsubstituted C1-C10 alkyl group.
[0126] For example, in Equations 2 and 3, R 1 and R 2 At least one of may be an unsubstituted C3-C10 alkyl group, and R 7 and R 8At least one of may be an unsubstituted C3-C10 alkyl group. The term "substituted" used in Formulae 2 and 3 is as described above, and thus a detailed description thereof will not be given.
[0127] In the composite electrolyte layer, the anion of the ionic liquid may include BF 4 - , AsF 6 - , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2 - ,(CF 3 SO 2 ) 3 C - 、NO 3 - , CH 3 COO - , Cl - Br - ,I - 、SO 4 2- CF 3 SO 3 - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - , SF5 CF 2 SO 3 - , SF 5 CHF 2 SO 3 - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - , C 2 N 3 - , and (O(CF 3 ) 2 C 2 (CF 3 ) 2 O) 2 PO - 、(FSO 2 ) 2 N - ,(CF 3 SO 2 ) 2 N - , or a combination thereof.
[0128] The composite electrolyte layer may further include a polymer ionic liquid. Since the composition of the polymer ionic liquid is as described above, a detailed description thereof will not be given.
[0129] Lithium Metal Batteries
[0130] Figure 2A and 2B Schematic diagrams illustrating structures of lithium metal batteries 20 and 20 ′ according to one or more embodiments.
[0131] Reference Figure 2A and 2B, the lithium metal battery 20 or 20' has a structure in which the positive electrode current collector 21 or 21', the positive electrode active material layer 22 or 22', the composite electrolyte layer 23 or the composite electrolyte layer 23a' containing a polymer ionic liquid, and the negative electrode 24 or 24' are stacked in sequence. Optionally, an intermediate layer (not shown) may be further inserted between the composite electrolyte layer 23 and the negative electrode 24 or between the composite electrolyte layer 23a' containing a polymer ionic liquid and the negative electrode 24'. For example, the intermediate layer (not shown) may be a separator. The separator may include polyethylene, polypropylene, or polyvinylidene fluoride, or have a multilayer structure including two or more thereof. The separator may be a mixed multilayer separator such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, and a polypropylene / polyethylene / polypropylene three-layer separator. The separator may further include an electrolyte containing a lithium salt and an organic solvent.
[0132] Figure 3 2 is a schematic diagram illustrating the structure of a lithium metal battery 30 according to an embodiment.
[0133] Reference Figure 3 The lithium metal battery 30 includes a positive electrode 31 and a negative electrode 32 and further includes a battery case 34 accommodating the positive electrode 31 and the negative electrode 32 .
[0134] The positive electrode 31 may include the above-mentioned composite positive electrode. The composite positive electrode 31 may be prepared by coating a positive electrode active material and the composite electrolyte on the surface of a positive electrode current collector formed of aluminum, etc. Alternatively, the composite positive electrode 31 may be prepared by casting a positive electrode active material and the composite electrolyte on a separate support and laminating a positive electrode active material film separated from the support on a current collector.
[0135] The negative electrode 32 may include lithium metal or a lithium alloy. The lithium alloy includes lithium and a metal / metalloid or its oxide that can be alloyed with lithium. The metal / metalloid or its oxide that can be alloyed with lithium may be Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y' alloy (wherein Y' is an alkali metal, an alkaline earth metal, a 13-16 group element, a transition metal, a rare earth element, or any combination thereof (except Si)), or Sn-Y' alloy (wherein Y' is an alkali metal, an alkaline earth metal, a 13-16 group element, a transition metal, a rare earth element, or any combination thereof (except Sn)), or MnO x (0 <x≤2)。
[0136] The element Y' can be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or any combination thereof. For example, the oxide of the metal / metalloid capable of alloying with lithium can be lithium titanium oxide, vanadium oxide, lithium vanadium oxide, SnO 2 , SiO x (0 < x < 2), etc.
[0137] Optionally, a protective layer (not shown) can be formed on the negative electrode 32. The thickness of the protective layer can be 5 micrometers (μm) or less. The protective layer can be a solid-type protective layer.
[0138] The above composite electrolyte layer can be interposed between the positive electrode 31 and the negative electrode 32.
[0139] The lithium metal battery can be formed, for example, as a unit cell battery having a positive electrode / separator / negative electrode structure, a dual cell battery having a positive electrode / separator / negative electrode / separator / positive electrode structure, or a stacked battery having a structure in which the unit cell is repeated, but the embodiments are not limited thereto.
[0140] The lithium metal battery can be a primary lithium battery or a secondary lithium battery. For example, the lithium metal battery can be a lithium metal secondary battery. However, the shape of the battery is not particularly limited and the lithium metal battery can have a coin, button, sheet, stacked body, cylindrical, thin film, or angular shape. Moreover, the lithium metal battery can be applied to large batteries used in electric vehicles, etc. For example, the lithium metal battery can be used in hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs). In addition, the lithium metal battery can be used in applications that require a large amount of energy storage. For example, the lithium metal battery can be used in electric bicycles and power tools.
[0141] A method for preparing the composite electrolyte according to another embodiment includes combining a lithium salt, a solid electrolyte, and an ionic liquid, wherein the solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof. For example, the lithium salt and the solid electrolyte can be added to the ionic liquid. The term "add" is used broadly herein to include impregnation, etc.
[0142] Alternatively, a composite positive electrode precursor including a positive electrode active material layer precursor containing a plurality of solid electrolyte particles and a plurality of positive electrode active material particles can be prepared. Then the ionic liquid can be added to the positive electrode active material layer precursor to form the composite positive electrode.
[0143] For example, according to an embodiment of the method for preparing the composite electrolyte, the ionic liquid can be filled or arranged in the pores between the particles of the sulfide solid electrolyte and the oxide solid electrolyte by immersing the solid electrolyte in an electrolyte prepared by adding the lithium salt to the ionic liquid, wherein the solid electrolyte is the sulfide solid electrolyte, the oxide solid electrolyte, or a combination thereof. The method for preparing the composite electrolyte is suitable for large-scale manufacturing due to its ease.
[0144] Hereinafter, the present disclosure will be described in more detail according to the following examples and comparative examples. However, the following examples are presented only to illustrate the present disclosure, and the scope of the present disclosure is not limited thereto.
[0145] Example
[0146] Preparation of composite electrolytes
[0147] Example 1: Preparation of composite electrolyte
[0148] Weigh Li in stoichiometric molar ratio 2 S powder (Sigma Aldrich, 99%), P 2 S 5 Powder (SigmaAldrich, 99%), and LiCl powder (Acros Organic, 99%) were mixed. The mixture was mechanically ground using zirconium oxide balls and then subjected to high-energy ball milling at a speed of 600 rpm for about 20 hours to obtain a crushed mixture. The crushed mixture was placed in an electric autoclave under an argon atmosphere and annealed at 550° C. for about 5 hours to obtain Li 6 PS 5 Cl sulfide solid electrolyte.
[0149] The obtained Li 6 PS 5 Cl was impregnated in 1-methyl-1-propylpyrrolidine bis(fluorosulfonyl)imide as an ionic liquid (PY1,3-FSI, with a dielectric constant of 13.02) and 1M lithium bis(fluorosulfonyl)imide (LiFSI) as a lithium salt to prepare a composite electrolyte. In the composite electrolyte, the weight ratio of the ionic liquid to the sulfide solid electrolyte is 10:90. When measured by a 2-probe method at room temperature (25°C) using an amplitude of 10 millivolts (mV) and a frequency of about 915 megahertz (MHz), the dielectric constant of the mixture of the ionic liquid PY1,3-FSI and the lithium salt LiFSI is about 6.0.
[0150] Example 2: Preparation of composite electrolyte
[0151] A composite electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the ionic liquid to the sulfide solid electrolyte in the composite electrolyte was 50:50 instead of 10:90.
[0152] Example 3: Preparation of composite electrolyte
[0153] A composite electrolyte was prepared in the same manner as in Example 1, except that a mixed electrolyte of PY1,3-FSI as an ionic liquid and 2 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as a lithium salt was used instead of a mixed electrolyte of PY1,3-FSI as an ionic liquid having a dielectric constant of 13.02 and 1 M LiFSI as a lithium salt.
[0154] Comparative Example 1: Preparation of Electrolyte
[0155] A sulfide solid electrolyte was prepared in the same manner as in Example 1, except that the mixing weight ratio of the ionic liquid to the sulfide solid electrolyte in the composite electrolyte was 0:100 instead of 10:90.
[0156] Comparative Example 2: Preparation of Electrolyte
[0157] An electrolyte containing an ionic liquid was prepared in the same manner as in Example 1, except that the mixing weight ratio of the ionic liquid to the sulfide solid electrolyte in the composite electrolyte was 100:0 instead of 10:90.
[0158] Comparative Example 3: Preparation of composite electrolyte
[0159] A composite electrolyte was prepared in the same manner as in Example 1, except that 1-ethyl-3-methylimidazole bis(fluorosulfonyl)imide was used. The mixed electrolyte of PY1,3-FSI with a dielectric constant of 13.02 as the ionic liquid and 1 M LiFSI as the lithium salt was replaced by a mixed electrolyte of EMI-FSI (with a dielectric constant of 14.63) and 1 M LiFSI.
[0160] Comparative Example 4: Preparation of composite electrolyte
[0161] A composite electrolyte was prepared in the same manner as in Example 1, except that a mixed electrolyte of EMI-FSI having a dielectric constant of 14.63 as an ionic liquid and 2 M LiFSI as a lithium salt was used instead of a mixed electrolyte of PY1,3-FSI having a dielectric constant of 13.02 as an ionic liquid and 1 M LiFSI as a lithium salt.
[0162] Preparation of composite cathode
[0163] Example 4: Preparation of composite positive electrode
[0164] The composite cathode was prepared according to the following process. In addition, all procedures of the composite cathode were carried out in an inert atmosphere.
[0165] LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O 2 , the composite electrolyte prepared according to Example 1, and carbon black (Super-P, Timcal Ltd.) as a conductive agent were uniformly mixed in a mortar at a weight ratio of 60:30:10 to prepare a positive electrode active material layer composition (positive electrode mixture). 200 mg of the positive electrode active material layer composition (positive electrode mixture) was inserted into a molding jig and 7 tons / cm 2 The positive electrode active material layer composition (positive electrode mixture) is formed into a disc by compression molding at a pressure of . The disc-shaped positive electrode active material layer composition (positive electrode mixture) is stacked on an aluminum film as a positive electrode current collector to prepare a composite positive electrode with a positive electrode active material layer.
[0166] Example 5: Preparation of composite positive electrode
[0167] A composite positive electrode was prepared in the same manner as in Example 4, except that LiNi 0.8 Co 0.1 Mn 0.1 O 2 , the composite electrolyte prepared according to Example 2, and carbon black (Super-P, Timcal Ltd.) as a conductive material were used in a weight ratio of 90:8:2 instead of 60:30:10. The composite density of the composite positive electrode was 3.05 g / cm3 (g / cm 3 ).
[0168] Example 6: Preparation of composite positive electrode
[0169] A composite cathode was prepared in the same manner as in Example 4, except that the composite electrolyte prepared according to Example 3 was used.
[0170] Comparative Example 5: Preparation of composite positive electrode
[0171] A composite cathode was prepared in the same manner as in Example 4, except that the electrolyte prepared according to Comparative Example 1 was used.
[0172] Comparative Example 6: Preparation of composite positive electrode
[0173] A composite positive electrode was prepared in the same manner as in Example 4, except that LiNi 0.8 Co 0.1 Mn 0.1 O 2 , the electrolyte prepared according to Comparative Example 1, and carbon black (Super-P, Timcal Ltd.) as a conductive agent were used in a weight ratio of 90:8:2 instead of LiNi as a positive electrode active material. 0.8 Co 0.1 Mn 0.1 O 2 , the composite electrolyte prepared according to Example 1, and carbon black (Super-P, Timcal Ltd.) as a conductive agent were used in a weight ratio of 60:30:10. The density of the composite positive electrode mixture was 2.87 g / cm 3 .
[0174] Comparative Example 7: Preparation of composite positive electrode
[0175] A composite cathode was prepared in the same manner as in Example 4, except that the electrolyte prepared according to Comparative Example 2 was used.
[0176] Comparative Example 8: Preparation of composite positive electrode
[0177] A composite cathode was prepared in the same manner as in Example 4, except that the composite electrolyte prepared according to Comparative Example 3 was used.
[0178] Comparative Example 9: Preparation of composite positive electrode
[0179] A composite cathode was prepared in the same manner as in Example 4, except that the composite electrolyte prepared according to Comparative Example 4 was used.
[0180] Preparation of lithium metal batteries
[0181] Example 7: Preparation of lithium metal battery
[0182] The lithium metal battery was prepared according to the following process. In addition, all procedures of the lithium metal battery were carried out in an inert atmosphere.
[0183] The composite cathode according to Example 4 and the composite electrolyte layer of the composite electrolyte according to Example 1 were inserted into a molding jig and heated at 7 tons / cm 2 The composite electrolyte layer and the composite positive electrode are integrated by compression molding.
[0184] Subsequently, a lithium metal thin film (having a thickness of about 20 μm) formed on a copper thin film as a negative electrode current collector was inserted into a molding jig and 2The composite electrolyte layer formed on the composite positive electrode was integrated by pressure compression molding to prepare a lithium metal battery for testing.
[0185] Examples 8 and 9: Preparation of lithium metal batteries
[0186] A lithium metal battery for testing was prepared in the same manner as in Example 7, except that the composite positive electrodes according to Examples 5 and 6 were used instead of the composite positive electrode according to Example 4.
[0187] Comparative Examples 10-14: Preparation of Lithium Metal Batteries
[0188] A lithium metal battery for testing was prepared in the same manner as in Example 7, except that the composite positive electrodes according to Comparative Examples 5 to 9 were used instead of the composite positive electrode according to Example 4.
[0189] Analysis of composite electrolytes and evaluation of unit cell resistance
[0190] Analytical Example 1: X-ray Diffraction (XRD)
[0191] The composite electrolyte or electrolyte according to Example 3 and Comparative Examples 1-3 was heated at 7 tons / cm 2 The discs were pressed at a pressure of 100 to obtain discs having a diameter of about 0.9 mm and a thickness of about 1 mm. The discs were maintained (i.e., kept at an open circuit voltage) for 24 hours and subjected to X-ray diffraction (XRD) analysis using CuKα radiation. The results are shown in Figure 4 middle.
[0192] X-ray diffraction was performed using a Rigaku RINT2200HF+ diffractometer using Cu Kα radiation. carried out.
[0193] Reference Figure 4 , it was confirmed that the Bragg diffraction angle (degrees, 2 theta, 2θ) value indicating the peak position of the composite electrolyte according to Example 3 did not change when compared with the electrolyte or composite electrolyte according to Comparative Examples 1-3. Therefore, no chemical change was observed in the composite electrolyte according to Example 3 when compared with the electrolyte or composite electrolyte according to Comparative Examples 1-3.
[0194] Analytical Example 2: Raman spectroscopy
[0195] The composite electrolyte or electrolyte according to Example 3 and Comparative Examples 1-3 was heated at 7 tons / cm 2 The disc was pressed at a pressure of 100 to obtain a disc having a diameter of about 0.9 mm and a thickness of about 1 mm. The disc was maintained (i.e., kept at an open circuit voltage) for 24 hours and Raman spectroscopy was performed. The results are shown in Figure 5 middle.
[0196] Raman spectroscopy was performed using an RM-1000 Invia instrument (514 nm, Ar + Ion laser, Renishaw).
[0197] Reference Figure 5 , in the composite electrolyte and electrolyte according to Example 3 and Comparative Examples 1-3 at about 425 cm -1 (cm -1 ) obtains the maximum absorption peak at the Raman shift of about 425cm -1 The maximum absorption peak obtained at (PS 4 ) 3- Therefore, it can be confirmed that there is no chemical change in the chemical structure of the composite electrolyte and the electrolyte according to Example 3 and Comparative Examples 1-3.
[0198] Analytical Example 3: Ion Chromatography
[0199] The Cl detected from the decomposition products of the composite electrolytes according to Examples 1 and 3 and Comparative Examples 3 and 4 with respect to time was evaluated by ion chromatography. - The amount of anions (i.e., Cl eluted from the composite electrolyte) - The results are shown in Table 1 below, where the amount of anions eluted is reported in parts per million (ppm) by weight based on the total weight of the composite electrolyte.
[0200] The ion chromatography was performed by extracting each of the composite electrolytes according to Examples 1 and 3 and Comparative Examples 3 and 4 using a syringe after about 24 hours, and filtering the composite electrolyte using a polyvinylidene fluoride (PVdF) filter (pore size of 0.45 μm, Sigma Aldrich). The ion chromatography was performed using a Dionex ICS-5000+HPIC system (Thermoscientific, San Jose, CA).
[0201] Table 1
[0202] <![CDATA[Amount of Cl - anions eluted from the composite electrolyte (ppm)]]> Example 1 2.7 Example 3 4.95 Comparative Example 3 73.62 Comparative Example 4 33.07
[0203] Referring to Table 1, the Cl eluted from the composite electrolytes according to Examples 1 and 3 - The amount of anions was much lower than that of the composite electrolytes according to Comparative Examples 3 and 4. In addition, the Cl eluted from the composite electrolytes according to Examples 1 and 3 - The amounts of anions were 2.7 ppm and 4.95 ppm, which were less than 10 ppm.
[0204] Evaluation Example 1: Ionic Conductivity
[0205] The composite electrolyte or electrolyte according to Examples 1 and 3 and Comparative Examples 1 and 2 was heated at 7 tons / cm 2 The disc was pressed at a pressure of 100 to obtain a disc having a diameter of about 0.9 mm and a thickness of about 1 mm. The ionic conductivity of the disc was measured before (initial) and after being maintained for 100 hours. As used herein, the term "maintain" means to maintain at an open circuit voltage. The results are shown in Figure 6 and Table 2. Ionic conductivity is reported as millisiemens / cm (mS / cm).
[0206] The ionic conductivity was evaluated by measuring the resistivity by applying a voltage bias of 10 mV in a frequency range of about 0.1 Hz to about 1 MHz while scanning the temperature, and converting the resistivity into ionic conductivity. The evaluation of the ionic conductivity was performed using the ionic conductivity reduction rate (%) represented by the following equation 1.
[0207] Equation 1
[0208] Ion conductivity reduction rate (%) = [(initial ion conductivity - ion conductivity after 100 hours of maintenance) / (initial ion conductivity)] x 100
[0209] Table 2
[0210]
[0211] Reference Figure 6 and Table 2, the composite electrolytes according to Examples 1 and 3 have lower ion conductivity reduction rates than the electrolytes according to Comparative Examples 1 and 2. The ion conductivity reduction rates of the composite electrolytes according to Examples 1 and 3 are both less than 15%.
[0212] Evaluation Example 2: Evaluation of Impedance-Interface Resistance
[0213] The impedance characteristics of the test lithium metal batteries according to Comparative Example 10 and Example 7 were evaluated.
[0214] The impedance was measured by using an impedance analyzer (Solartron 1260A impedance / gain-phase analyzer) according to the 2-probe method at 25°C for about 10 6 The initial impedance of the test lithium metal batteries according to Comparative Example 10 and Example 7 was evaluated by measuring the resistance while applying a voltage bias of 10 mV in a frequency range of 10 Hz to about 0.1 MHz. Then, each of the test lithium metal batteries was charged at a rate of 0.1 C under the same conditions (cutoff window: 3.0-4.3 V) in a constant current mode and its impedance was measured. The results of the Nyquist plots are shown in Fig. 7A and 7B In. Fig. 7A and7B In the embodiment, the interfacial resistance between the composite positive electrode and the electrolyte or composite electrolyte is determined based on the position and size of the semicircle.
[0215] Reference Fig. 7A and 7B Although the initial interface resistance of the test lithium metal battery according to Example 7 is similar to the initial interface resistance of the test lithium metal battery according to Comparative Example 10 (before charging at a rate of 0.1C), the interface resistance of the lithium metal battery according to Example 7 after charging at a rate of 0.1C is reduced to about 1 / 8 of the interface resistance of the test lithium metal battery according to Comparative Example 10 after charging at a rate of 0.1C.
[0216] According to the composite electrolyte and the method for preparing the composite electrolyte according to the present disclosure, the chemical reaction with the electrolyte can be reduced to maintain or improve ion conductivity. Therefore, the composite positive electrode and lithium metal battery each including the composite electrolyte can have increased energy density and discharge capacity as well as improved high rate characteristics and life characteristics.
[0217] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for purposes of limitation. Descriptions of features or aspects within each embodiment should typically be considered as available for other similar features or aspects in other embodiments.
[0218] Although one or more embodiments have been described with reference to the drawings, it will be understood by those of ordinary skill in the art that various changes in form and details may be made therein without departing from the spirit and scope as defined by the following claims.
Claims
1. A composite electrolyte, comprising: a lithium salt; a solid electrolyte, wherein the solid electrolyte is a sulfide solid electrolyte; and an ionic liquid, wherein a mixture of the ionic liquid and the lithium salt has a dielectric constant of 4 - 12, and the amount of halogen ions eluted from the composite electrolyte after impregnating the solid electrolyte in the ionic liquid and the lithium salt for 24 hours, measured by ion chromatography, is less than 25 parts per million by weight, based on the total weight of the composite electrolyte, wherein the sulfide solid electrolyte comprises a solid electrolyte represented by Formula 1: Formula 1 Li a M b P.S. c A d wherein, in Formula 1, 0 < a ≤ 6, 0 ≤ b ≤ 6, 0 < c < 6, and 0 ≤ d ≤ 6; M is Ge, Sn, or Si; and A is F, Cl, Br, or I, the ionic liquid comprises a cation represented by Formula 2, Formula 3, or a combination thereof: Formula 2 Formula 3 wherein, in Formulas 2 and 3, X is independently N or P; R1, R2, R7, and R8 are each independently a substituted or unsubstituted C1 - C30 alkyl group or a substituted or unsubstituted C2 - C20 alkenyl group; R3, R4, R5, R6, R9, R 10 , R 11 , R 12 , and R 13 are independently hydrogen, halogen, hydroxyl, cyano, -C(=O)R a 、-C(=O)OR a 、-OCO(OR a )、-C=N(R a ),-SR a 、-S(=O)R a 、-S(=O)2R a 、-OR a , substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted C2-C20 alkenyl, substituted or unsubstituted C2-C20 alkynyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C6-C30 aryloxy, substituted or unsubstituted C6-C30 heteroaryl, or a combination thereof, wherein each R a are independently hydrogen, C1-C10 alkyl, or C6-C20 aryl; and at least one of R1 and R2 is an unsubstituted C1 - C10 alkyl group, and at least one of R7 and R8 is an unsubstituted C1 - C10 alkyl group.
2. The composite electrolyte according to claim 1, wherein the amount of the lithium salt in the ionic liquid is 1 mole per liter or more.
3. The composite electrolyte according to claim 1, wherein the lithium salt is LiSCN, LiN(CN)2, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiCl, LiF, LiBr, LiI, LiB(C2O4)2, LiBF4, LiBF3(C2F5), lithium difluoro(oxalato)borate, LiN(SO2CF3)2, LiN(SO2F)2, LiCF3SO3, LiAsF6, LiSbF6, LiClO4, or a combination thereof.
4. The composite electrolyte according to claim 1, wherein the weight ratio of the solid electrolyte to the ionic liquid is 0.1:99.9 - 90:
10.
5. The composite electrolyte according to claim 1, wherein the ionic liquid comprises the following anions: BF4 - 、AsF6 - 、SbF6 - 、AlCl4 - 、HSO4 - 、ClO4 - 、CH3SO3 - CF3CO2 - 、(CF3SO2)3C - 、NO3 - 、CH3COO - , Cl - Br - ,I - 、SO4 2- CF3SO3 - 、(C2F5SO2)2N - 、(C2F5SO2)(CF3SO2)N - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、SF5CF2SO3 - 、SF5CHFCF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、C2N3 - 、(O(CF3)2C2(CF3)2O)2PO - 、(FSO2)2N - 、(CF3SO2)2N - , or a combination thereof.
6. The composite electrolyte according to claim 1, further comprising a liquid electrolyte, a polymeric ionic liquid, or a combination thereof, wherein the polymeric ionic liquid is a compound represented by Formula J or a compound represented by Formula K: Formula J In Formula J, R"1 and R"3 are each independently hydrogen, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C2-C30 heteroaryl, or substituted or unsubstituted C4-C30 carbocyclic group, R"2 is a simple chemical bond, C1-C30 alkylene, C6-C30 arylene, C2-C30 heteroarylene, or C4-C30 divalent carbocyclic group, Z - is the anion of the polymer ionic liquid, and n is 500-2800; Formula K In formula K, Y - With formula J Z - The same is defined, and n is 500-2800.
7. A lithium metal battery, comprising: a composite positive electrode including a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer is disposed on the positive electrode current collector and includes a positive electrode active material and the composite electrolyte according to any one of claims 1 - 6; a lithium negative electrode including lithium metal or a lithium alloy; and a composite electrolyte layer disposed between the positive electrode active material layer and the lithium negative electrode and including a lithium salt, an ionic liquid, and a solid electrolyte, wherein the solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof. 8 . The lithium metal battery according to claim 7 , wherein the amount of the positive electrode active material in the positive electrode active material layer is 60 parts by weight or more based on 100 parts by weight of the positive electrode active material layer. 9 . The lithium metal battery according to claim 7 , wherein the amount of the composite electrolyte in the positive electrode active material layer is 5 parts by weight or more based on 100 parts by weight of the positive electrode active material layer. 10 . The lithium metal battery of claim 7 , wherein the positive electrode active material layer further comprises a conductive agent, a binder, or a combination of a conductive agent and a binder.
11. The lithium metal battery of claim 7, wherein the positive electrode active material layer comprises: a plurality of positive electrode active material particles; a plurality of solid electrolyte particles, wherein the plurality of solid electrolyte particles are mixed with the plurality of positive electrode active material particles; as well as a plurality of pores between adjacent positive electrode active material particles, between adjacent positive electrode active material particles and the solid electrolyte particles, between adjacent solid electrolyte particles, or a combination thereof, The ionic liquid is disposed in at least one pore between adjacent positive electrode active material particles, in at least one pore between adjacent positive electrode active material particles and the solid electrolyte particles, in at least one pore between adjacent solid electrolyte particles, or a combination thereof.
12. The lithium metal battery according to claim 7, wherein the ionic conductivity of the composite electrolyte of the positive electrode active material layer decreases by 15% or less relative to the initial ionic conductivity after 100 hours at an open circuit voltage. 13 . The lithium metal battery of claim 7 , wherein the amount of the ionic liquid in the composite electrolyte layer is less than 50 parts by weight based on 100 parts by weight of the composite electrolyte layer.
14. The lithium metal battery of claim 7, wherein the lithium salt of the composite electrolyte layer is LiSCN, LiN(CN)2, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiCl, LiF, LiBr, LiI, LiB(C2O4)2, LiBF4, LiBF3(C2F5), lithium difluoro(oxalato)borate, LiN(SO2CF3)2, LiN(SO2F)2, LiCF3SO3, LiAsF6, LiSbF6, LiClO4, or a combination thereof.
15. The lithium metal battery of claim 7, wherein the ionic liquid in the composite electrolyte layer comprises a cation represented by Formula 2, Formula 3, or a combination thereof: Formula 2 Formula 3 in, In equations 2 and 3, X is N or P; R1, R2, R7, and R8 are each independently a substituted or unsubstituted C1-C30 alkyl group or a substituted or unsubstituted C2-C20 alkenyl group; R3, R4, R5, R6, R9, R 10 , R 11 , R 12 , and R 13 are independently hydrogen, halogen, hydroxyl, cyano, -C(=O)R a 、-C(=O)OR a 、-OCO(OR a )、-C=N(R a ),-SR a 、-S(=O)R a 、-S(=O)2R a 、-OR a , substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted C2-C20 alkenyl, substituted or unsubstituted C2-C20 alkynyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C6-C30 aryloxy, substituted or unsubstituted C6-C30 heteroaryl, or a combination thereof, wherein each R a are independently hydrogen, C1-C10 alkyl, or C6-C20 aryl; and At least one of R1 and R2 is an unsubstituted C1-C10 alkyl group, and at least one of R7 and R8 is an unsubstituted C1-C10 alkyl group.
16. The lithium metal battery according to claim 7, wherein the ionic liquid of the composite electrolyte layer further comprises the following anions: BF4 - 、AsF6 - 、SbF6 - 、AlCl4 - 、HSO4 - 、ClO4 - 、CH3SO3 - CF3CO2 - 、(CF3SO2)3C - 、NO3 - 、CH3COO - , Cl - Br - ,I - 、SO4 2- CF3SO3 - 、(C2F5SO2)2N - 、(C2F5SO2)(CF3SO2)N - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - , (CF3)6P-, SF5CF2SO3-, SF5CHFCF2SO3-, CF3CF2(CF3)2CO-, (CF3SO2)2CH-, (SF5)3C-, C2N3-, (O(CF3)2C2(CF3)2O)2PO-, (FSO2)2N-, (CF3SO2)2N-, or a combination thereof.
17. A method for preparing the composite electrolyte according to any one of claims 1 to 6, the method comprising combining the lithium salt, the solid electrolyte, and the ionic liquid.
Citation Information
Patent Citations
Anti-her2 antibody-drug conjugate
KR1020180122038A
Method and device for controlling industrial processes
KR1020190062580A
Solid electrolyte and lithium battery comprising the solid electrolyte
US20170222244A1